Role of Biocontrol Agents in Management of Corm Rot of Saffron Caused by Fusarium oxysporum - Vishal Gupta; Krishna Kumar; Kausar Fatima; Vijay Kumar Razdan; Bhagwati Charan Sharma; Vidushi Mahajan; Pradeep Kumar Rai; Akash Sharma; Vikas Gupta; Mir Gulam Hassan; Rafakat Hussain (Agronomy, 2020)
Saffron (Crocus sativus L.) is considered as one of the most expensive spices. Fusarium corm rot of saffron, caused by Fusarium oxysporum, is known to cause severe yield losses worldwide. In the present study, efficacy of biocontrol agents (Trichoderma asperellum, Pseudomonas fluorescens, Pseudomonas aeruginosa, Pseudomonas putida, Bacillus stratosphericus, Bacillus pumilus, and Bacillus subtilis) along with a chemical fungicide, carbendazim, was evaluated for managing the corm rot of saffron. Under in vitro conditions, using dual culture and poison food techniques on potato dextrose agar, T. asperellum and carbendazim significantly reduced the mycelial growth of the pathogen F. oxysporum, with the inhibition of 62.76 and 60.27%, respectively, compared with control. Under field conditions, dipping of saffron corms in carbendazim and T. asperellum exhibited maximum reduction of 82.77 and 77.84%, respectively, in the disease incidence, during the first year of experiment. However, during the second year, maximum reduction in the incidence of corm rot (68.63%) was recorded with the T. asperellum. Moreover, the population density of F. oxysporum was also significantly reduced by 60 and 80.19% while using T. asperellum after 75 and 260 days of sowing of saffron corms, compared to its population before planting of corms. In case of growth promotion traits, such as sprouting and flowering, biocontrol treatments reduced the number of days (average) of sprouting and flower emergence after sowing, compared to control.